O PROGRAMA CONTA PRA MIM E O HOMESCHOOLING: DIÁLOGOS COM O ENSINO DA LEITURA - Ferreira, Ana Carolina de Oliveira (2022)
This research aims at understanding the program entitled Conta pra Mim, launched by the Ministry of Education (MEC), and its relation with the speeches regarding the implementation of homeschooling in Brazil. It seeks, at first, to identify researches that dialogue with the issue homeschooling and with family literacy. By exploring the works, it verifies that, mostly, do not present any positioning that goes against homeschooling. In addition, the literacy agenda is not a recurrent event due to the characteristics of homeschooling in the country. The work is strongly based on the dissertation in the bakhtinian perspective of language, with a qualitative approach. Therefore it comprehends that the utterances produced compose the discursive communication chain about the Conta pra Mim program, in articulation with homeschooling. It catalogs as methodology the qualitative approach, carrying out a document research. By investigating the context in which the program was developed, it stands out that the education privatization scenario collaborates with the validation of homeschooling. The Conta pra Mim program defends that literacy must occur in homes, also assumes the privatization of such practice concerning the domestic space. Thus, even though affirming to be tied to the school, the program shows an approximation with the homeschooling precepts, that way, the Conta pra Mim program pulls away literacy, mainly the reading skill, from the public space. This study recognizes that the production of utterances about literacy, developing it as a human being collective practice, is fundamental in order to have it guaranteed as right. By these means, this research defends that literacy must occur in schools, based on human rights.